Impact of Ecologically Unfriendly Environment on the Formation of Thyroid Pathology in Children Against Iodine Deficiency - N.S. Kosmynina; O.Z. Gnateyko; S.O. Pechenyk; G.S. Chaykovska (Zaslavsky O.Yu., 2014)
By prevalence among thyroid pathological conditions in Ukraine, the diffuse nontoxic goiter is dominated, the frequency of which, in addition to iodine deficiency, is influenced by anthropogenic pollution of environment. The article evaluated the role of the negative impact of polluted environment on the formation of thyroid disease in children from ecologically unfriendly region on the background of endemic iodine deficiency compared with children from ecologically friendly area of iodine deficiency. It has been determined the frequency of diffuse endemic goiter in children from studied groups according to palpation and ultrasonography. The functional state of the pituitary-thyroid system in children living in iodine deficiency environmentally unfriendly and ecologically friendly areas has been researched.